Insufficient recovery of thymopoiesis predicts for opportunistic infections in allogeneic hematopoietic stem cell transplant recipients - Wils, Evert-Jan (Ferrata Storti Foundation, 2011)
BACKGROUND: Recovery of thymopoiesis after allogeneic hematopoietic stem cell transplantation is considered pivotal for full immune competence. However, it is still unclear to what extent insufficient recovery of thymopoiesis predicts for subsequent opportunistic infections and non-relapse mortality. DESIGN AND METHODS: A detailed survey of all post-engraftment infectious complications, non-relapse mortality and overall survival during long-term follow-up was performed in 83 recipients of allogeneic stem cell grafts after myeloablative conditioning. Recovery of thymopoiesis was assessed using analysis of signal joint T-cell receptor rearrangement excision circles. The impact of recovery of thymopoiesis at 2, 6, 9 and 12 months post-transplantation on clinical outcome beyond those time points was evaluated by univariate and multivariate Cox regression analyses. RESULTS: The cumulative incidence of severe infections at 12 months after transplantation was 66% with a median number of 1.64 severe infectious episodes per patient. Patients in whom thymopoiesis did not recover were at significantly higher risk of severe infections according to multivariable analysis. Hazard ratios indicated 3- and 9-fold increases in severe infections at 6 and 12 months, respectively. Impaired recovery of thymopoiesis also translated into a higher risk of non-relapse mortality and outweighed pre-transplant risk factors including age, donor type, and disease risk-status. CONCLUSIONS: These results indicate that patients who fail to recover thymopoiesis after allogeneic hematopoietic stem cell transplantation are at very high risk of severe infections and adverse clinical outcome.